Implementing Lean Six Sigma to enhance operational efficiency and reduce waste in essential food storage SMES: a case study - Guerrero Villa, Cristian David (2025)
Small and medium-sized enterprises (SMEs) in the essential food storage sector play a crucial role globally, especially in Latin America and Peru. These businesses are vital for ensuring the availability and distribution of necessities. However, they face challenges, including low operational efficiency and high rates of defective products, which hinder their competitiveness and sustainability. Addressing these issues is essential for improving productivity, profitability, and economic development. This research addresses these challenges by proposing a Lean Six Sigma production model integrated with 5S, Poka Yoke, and Standardized Work tools. The model aims to streamline processes, reduce defects, and optimize resource utilization. The study implemented these tools in a case study to demonstrate their effectiveness in enhancing performance and competitiveness. Key findings include a significant improvement in operational efficiency and waste reduction. The 5S methodology increased compliant activities from 63.3% to 70%, while Poka Yoke reduced defective products by 59% and packaging time by 34%. Standardized Work reduced operation times by an average of 48% and product waste by 36%.